Accuracy of screening tools for Pap smears in general practice. Issue 3 (1st July 2016) - Harding, Catherine; Seal, Alexa; Duncan, Geraldine; Huynh, Ronald; McWilliam, Robert; Pilotto, Louis; Blake, Stephanie; Mackey, Ken
Abstract : Background: Data extraction tools (DETs) are increasingly being used for research and audit of general practice, despite their limitations. Objective: This study explores the accuracy of Pap smear rates obtained with a DET compared to that of the Pap smear rate obtained with a manual file audit. Method: A widely available DET was used to establish the rate of Pap smears in a large multi-general practice (multi-GP) in regional New South Wales followed by a manual audit of patient files. The main outcome measure was identification of possible discrepancies between the rates established. Results: The DET used significantly underestimated the level of cervical screening compared to the manual audit. In some instances, the patient file contained phone/specialist record of Pap smear conducted elsewhere, which accounted for the failure of the DET to detect some smears. Those patients who had Pap smears whose pathology codes differed between time intervals, i.e. from different pathology providers or from within the same provider but using a different code, were less likely to have had their most recent Pap smear detected by the DET ( p < 0.001). Conclusion: Data obtained from DETs should be used with caution as they may not accurately reflect the rate of Pap smears from electronic medical records. How this fits in: DETs are increasingly being used for research and audit of general practice. This study explores the accuracy of Pap smear rates obtained with a DET compared to that of the Pap smear rate obtained with a manual file audit The DET tested significantly underestimated the level of cervical screening compared to manual screening. Data obtained from DETs should be used with caution as they may not accurately reflect the rate of Pap smears from electronic medical records.